2010
DOI: 10.2967/jnumed.110.080796
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose 18F-FDG PET/CT Enterography: Improving on CT Enterography Assessment of Patients with Crohn Disease

Abstract: The purpose of this study was to evaluate the diagnostic efficacy of low-dose, combined 18 F-FDG PET/CT enterography (PET/CTE), compared with CT enterography (CTE) alone, in the assessment of patients with Crohn disease. Methods: Thirteen patients with Crohn disease were prospectively enrolled in this pilot study and underwent abdominal-pelvic 18 F-FDG PET/CTE using neutral oral and intravenous contrast medium. The effective dose from PET/CTE was 17.7 mSv for the first 4 patients and 8.31 mSv for the last 9 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…The FDG dose of 185MBq was selected as the lowest dose that has provided meaningful data in a CD study 24 . Optimisation of radiation exposure was the reasoning behind the use of a low-dose CT for attenuation correction and segment localization, instead of a fulldose CT enterography protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FDG dose of 185MBq was selected as the lowest dose that has provided meaningful data in a CD study 24 . Optimisation of radiation exposure was the reasoning behind the use of a low-dose CT for attenuation correction and segment localization, instead of a fulldose CT enterography protocol.…”
Section: Discussionmentioning
confidence: 99%
“…A target dose of 185MBq of 18 F-FDG in 10ml of normal saline was administered intravenously, followed by a saline flush. The patients then were asked to rest semi-recumbently in a quiet room, and, in keeping with similar protocols in the literature 10,11,[21][22][23][24] , they were given between 800-1200ml of an oral bowel distension, agent. 2.5% mannitol was used according to local protocol in our institution.…”
Section: Pet Scanningmentioning
confidence: 99%
“…Combining the morphologic patterns obtained by CT enterography with the 18 F-FDG metabolic activity obtained by PET, PET-CT enterography as a single test may provide accurately fused morphologic, physiologic, and metabolic imaging, useful in the diagnosis, evaluation of activity, follow-up, and objective assessment of CD [92] . Groshar et al [93] showed a statistically significant difference in mean SUV max among the different mural patterns revealed on CT enterography: intramural edema (active inflammation), intramural soft tissue attenuation (inflammatory infiltrate), and intramural fat (chronic inflamma- tion).…”
Section: Pet-ct Enterographymentioning
confidence: 99%
“…However, physiologic uptake of FDG by the intestine can lead to false positive results [94,95] . Moreover, the effective dose from PET-CT is actually too high for pediatric patients [92] .…”
Section: Pet-ct Enterographymentioning
confidence: 99%
“…There is still limited evidence on these imaging methods both in adult and in pediatric IBO patients, but there is a good correlation between PET findings and disease activity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: General Remarks Andfuture Perspectivesmentioning
confidence: 99%